2001
DOI: 10.1007/s002560100363
|View full text |Cite
|
Sign up to set email alerts
|

Anterior approach for knee arthrography

Abstract: All the arthrograms were technically successful. The anterior approach to knee MRA has greater technical ease than the traditional approach with little patient discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…Aspiration or injection via the LMP or MMP approaches has been reported to be uncomfortable for patients, and can be painful if access is difficult. These approaches can be difficult when patients tense the thigh extensors; in the obese; and in patients with patellofemoral arthrosis12). Wind and Smolinski13) have suggested that, as lateral joint line injections (ie LMP) may not be reliable for routine injections of low volumes of fluid into the knee joint as it results in good IA delivery less than half the time with a high incidence of soft-tissue infiltration, a superomedial or superolateral approach should be used instead.…”
Section: Approaches To Aspiration or Injection Of The Knee Jointmentioning
confidence: 99%
See 3 more Smart Citations
“…Aspiration or injection via the LMP or MMP approaches has been reported to be uncomfortable for patients, and can be painful if access is difficult. These approaches can be difficult when patients tense the thigh extensors; in the obese; and in patients with patellofemoral arthrosis12). Wind and Smolinski13) have suggested that, as lateral joint line injections (ie LMP) may not be reliable for routine injections of low volumes of fluid into the knee joint as it results in good IA delivery less than half the time with a high incidence of soft-tissue infiltration, a superomedial or superolateral approach should be used instead.…”
Section: Approaches To Aspiration or Injection Of The Knee Jointmentioning
confidence: 99%
“…Shortt et al4) reported that only 7/64 (11%) of surveyed North American musculoskeletal radiologists preferentially utilised an arthroscopic approach for injection of the knee joint. Anterior techniques utilise an entry approach analogous to the portals used for knee arthroscopy12,21). These approaches are useful when the knee cannot be extended, or when there is only a minimal amount of fluid in the knee joint14).…”
Section: Approaches To Aspiration or Injection Of The Knee Jointmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the anteromedial approach 2,6 has been widely used, Jackson et al 2 found the lateral approach more successful in a series of 240 knee injections in patients with no clinical knee joint effusion. In addition, Roberts et al 7 found that the medial plica and a medial patella fat pad could cause difficulty with an intra-articular needle.…”
Section: Discussionmentioning
confidence: 98%